Análise da expressão de ligantes de células natural killer em linhagens celulares derivadas de carcinoma epidermóide oral submetidas à terapia fotodinâmica - Molon, Angela Cristina (2021)
The most common neoplasm in the oral cavity is the Oral Epidermoid Carcinoma (OEC). Diagnosis is usually late, and treatment is associated with radiotherapy and/or chemotherapy. Photodynamic therapy (PDT) occurs through the interaction of light with a photosensitizer (Ps), originating reactive oxygen species (ROS). A minimally invasive technique is the 5-ALA-PDT. It preserves functional and anatomical integrity, has few side effects, is selective for tumor cells, and has low toxicity, which favors the use of multiple cycles. Studies have already shown that a PDT is capable of modulating an immune response. Although its effect on the modulation of ligands for the activation of NK cells is not known, which are important in the antitumor immune response. Thus, this study aimed to analyze, in vitro, the effect of PDT on the viability of OEC-derived cell lines (ca1 and Luc4) as well as on the gene expression of Natural Killer cell ligands and the protein expression of HLA-ABC. Additionally, it was also evaluated the effect of the conditioned environment from the Luc4 cell line, on the expressions of NKG2D, Nkp30, Nkp44, as well as the NKp46 receptors from the NK92-MI cell line. For that, viability tests were performed by Cristal Violeta and Alamar blue. It was analyzed the gene expression of the ULBP1-4 and MICA/B genes by RT-qPCR after 3, 12, and 24 hours of treatment, as well as the expression of HLA-ABC, NKp30, NKp44, NKp46, and NKG2D by flow cytometry. The results demonstrate a decrease in cell viability in the PDT group in both lines. The gene expression data showed that only the ULBP1 gene increased after PDT in the Ca1 lineage and there was a reduction in the expression of ULBPs evaluated in the PDT group after 12 and 24 hours. On the other hand, there was an increase in the expression of ULBP1, ULBP3, and ULBP4 in the 5-ALA group after 12 hours, as well as of MICA/B after 3 and 24 hours of treatment. In addition, the LED treatment increased the expression of all genes obtained after 24 hours. In the Luc4 lineage, PDT increased the expression of ULBP1, ULBP3, ULBP4 genes after 3 and 12 hours of treatment; MICA/B in the 5-ALA after 12 hours; LED group after 24 hours and ULBP1 after 12 hours. In general, a reduction in the expression of ULPBs evaluated after 24 hours of PDT was observed. In the evaluation of HLA-ABC expression, there was a decrease in the Ca1 lineage of the PDT group when compared to the Control group. There was no statistical difference in the Luc4 lineage, and after 24 hours of cultivation in its conditioned environment, there was a decrease in the percentage of cells in the expression of NKG2D, NKp30, NKp44, and NKp46 in the PDT group compared to the Control group. Based on all of that, it can be concluded that a PDT module is the expression of activating ligands for NK cells.